PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERMUATAN SATUAN LIWUT DAN SUBUR MASYARAKAT KABUPATEN SIKKA UNTUK MENUMBUHKAN PROFIL BERKEBINEKAAN GLOBAL - Susanty, Petronela Ivoni; Mario Florentino; Paula Emerentiana; Agustina Fausta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The ultimate goal of learning mathematics is that students are able to formulate and express solutions to everyday mathematical problems. This means that innovations in learning mathematics must be in accordance with the environmental conditions of the education unit, in order to be able to answer problems in the environment. In addition, the government is also trying to form a Pancasila Student Profile meaning that students who have basic competencies and behaviors that are in line with the values of Pancasila. Hence, the researcher developed a math learning module containing the traditional units ‘liwut’ and ‘subur’ of Sikka Regency. This study aimed to determine whether the developed module was feasible to use in learning and whether it was able to foster global diversity profiles in order to succeed the Pancasila Student Profile. This research was a Research and Design study with the ADDIE model. The results of material expert validation obtained an average of 2.67, a feasibility percentage of 90.8%, and the results of media expert validation obtained an average of 2.65, a feasibility percentage of 88.33% and they were in the feasible category. Furthermore, the results of the product trial indicated that the average of student questionnaire response was 3.94, percentage of questionnaire response was 98.42% and they were in the very good category. Furthermore, the average results of the teacher response questionnaire were 3.84, the percentage of teacher questionnaire response was 96.08% and they were in the very good category. The percentage of the global diversity dimension questionnaire was 91.93% and it was in the very good category. The results indicated that the learning module was valid, feasible to use and able to foster a global diversity profile.